EVALUASI WAKTU TUNGGU PELAYANAN RESEP DI APOTEK RAWAT JALAN RUMAH SAKIT CITRA HUSADA KOTAWARINGIN BARAT - Effendi, Harun; Makani, Mawaqit; Sulistiyono, Luluk; Irawan, Yogie; Hatimah, Naimi Amalia; Rahimamullah, M Arsyad (STIKES Borneo Cendekia Medika, 2024)
The waiting time for medication services is the period required from the patient submitting a prescription to receiving the medication. The Ministry of Health has set a minimal standard of < 30 minutes for non-compounded prescriptions and < 60 minutes for compounded prescriptions. This study aims to determine the percentage of waiting times for outpatient prescription services at Citra Husada Hospital, Kotawaringin Barat. This descriptive study was conducted through direct observation and recording of the waiting time in the waiting time log form during April 2024. A total of 160 non-compounded prescriptions and 30 compounded prescriptions were analyzed. The average time required to process non-compounded prescriptions during the morning shift was 23.6 minutes, while the time for compounded prescriptions was 45 minutes. During the afternoon shift, the average time for noncompounded prescriptions was 23 minutes, and for compounded prescriptions, it was 47 minutes. The results of this study show that the average waiting time for prescription services at Citra Husada Hospital, Kotawaringin Barat, meets the minimum service standards set by the hospital.